Global Governance and the Universal Common Good - Williams LC, Thomas D. (Alpha Omega, 2010)
The author sets out to explain Pope Benedict XVI’s view of global governance, especially as expressed in his 2009 encyclical letter Caritas in Veritate. In so doing, the author first recognizes some of the more significant arguments against global governance, then goes on to suggest that much of the opposition to Benedict’s proposal stems from two misconceptions: (1) a failure to place Benedict’s statements in the social tradition of the Church, which has always asserted that every society, including global society, has need of a corresponding authority to insure the common good, and (2) confusion of the terms “global governance” with “world government.” The latter connotes a powerful, centralized political structure while the former allows for a subsidiary, multi-tiered approach to coordinating the world geo-political situation. The author asserts that Benedict’s proposals reflect tthis second approach. The final sections of the article look at two special cases where global governance seem particularly pressing: international conflict resolution and global economic development.